Disagreement Strategies in Online Communication: A Case Study of the Javanese Community in Yogyakarta - Putra, Dona Aji Karunia; Alek, Alek; Muttaqien, Muhammad Zainal (JOLLT Journal of Languages and Language Teaching, 2025)
Each language community has a unique disagreement strategy in online communication that reflects its cultural values and communication norms. Disagreement can be expressed differently depending on the medium used. In face-to-face communication, disagreement tends to be expressed indirectly and with mitigation. In online communication, disagreement tends to be expressed explicitly and without mitigation. This study describes the strategies for expressing disagreement in the Info Cegatan Jogja Group and the factors that cause the emergence of various disagreement strategies in the group. The study used a descriptive qualitative method to analyze sentences expressing disagreement in posts from the ICJ Facebook Group. The data sources were message walls and comment fields. The study identified four types of disagreement strategies: one-speech strategy, two-speech strategies, three-speech strategies, and four-speech strategies. Verbal communication is the primary strategy employed to express disagreement among ICJ members. The study found that most disagreements are classified as strong, based on the level of confrontation. Various disagreement strategies were identified, which can be attributed to factors such as social media dynamics, posting topics, gender dynamics, and cultural influences. Understanding strategies for managing disagreements and cultural norms surrounding it is essential for successful communication.